REPRESENTATION - Hall, Stuart; Evans, Jessica; Nixon, Sean (The Open University, 2013)
Since 1997 Representation has been the key go-to textbook for students learning the tools to question and critically analyze institutional and media texts and images. This long-awaited Second Edition update and refreshes the approaches to representation, signalling key developments in the field, addresses the emergence of new technologies, media formats, politics and theories, includes an entirely new chapter on celebrity culture and reality TV, offers new exercises, readings, images and examples for a new generation of students. This book will once again prove an indispensible resource for students and teachers in cultural and media studies.